Comparing Cerebralcare Granule and aspirin for neurological dysfunction in acute stroke in real‐life practice. Issue 1 (12th January 2016) - Zhao, Luqing; Liao, Lianming; Hu, Fengyun
Abstract: Background: Cerebralcare Granule (CG) is a polyherbal Chinese medicine that has been shown to have neuroprotective effects in experimental models of stroke. We compared the efficacy and safety of CG with aspirin in patients with acute stroke. Methods: For this open‐label, controlled trial, we recruited patients with angiographically confirmed strokes and US National Institutes of Health Stroke Scale (NIHSS) scores of 4–22 within 2 weeks of symptom onset; recruitment was performed at 55 sites in China. Patients received CG or aspirin. The primary efficacy end‐point was neurological function. Analyses were done by intention to treat. Patients were measured for NIHSS, Montreal Cognitive Assessment, and Mini‐Mental State Examination scores and Barthel index at baseline and at 4, 8, and 12 weeks after treatment. Results: Between January 2013 and January 2014, we treated 1963 patients with CG and 1288 patients with aspirin. Baseline NIHSS, Mini‐Mental State Examination, and Montreal Cognitive Assessment scores were comparable between the two groups. Patients in the CG group had a greater improvement than the aspirin group in terms of NIHSS ( P < 0.01) and Barthel index at 4, 8, and 12 weeks. At 12 weeks, patients in the CG group had a greater improvement than the aspirin group in terms of Mini‐Mental State Examination ( P < 0.01) and Montreal Cognitive Assessment ( P < 0.05). Adverse reactions were similar between the two groups. Conclusions: This large‐scale, controlled trial indicated that CG may be a useful treatment in the management of post‐stroke patients.